The impact of genetic counselling on females in fragile X families. Issue 12 (December 1994) - Curtis, G; Dennis, N; MacPherson, J
Abstract : We report a retrospective study over the period 1981-1992 of the reproductive histories of 27 women, from 21 families, who were known or possible fragile X carriers. Eighteen women had cytogenetic and DNA linkage studies to establish their carrier risk. They subsequently received definitive carrier status information following the cloning of the gene in 1991. The remaining nine women had cytogenetic and mutation studies only. For 11 of the women their carrier risk was modified over the 11 year period. The results suggest that these women at risk of having a son with fragile X have carefully considered their reproductive choices. Three of the six women who were initially sterilised have had, or are awaiting, a reversal of sterilisation following clarification of their carrier status. There were 10 pregnancies to 10 women. Seven of the pregnancies were to women at "high" (40-100%) risk of being a carrier, and in this group only one woman chose to continue the pregnancy without prenatal diagnosis. Three pregnancies were to women at "medium" or "low" (< 39%) risk of being a carrier. None of the three chose prenatal diagnosis and one affected male was born to this group.